A performance analysis of Brazilian public health: TOPSIS and neural networks application. Issue 9 (19th November 2018) - Araujo, Claudia Affonso Silva; Wanke, Peter; Siqueira, Marina Martins
Abstract : Purpose: The purpose of this paper is to estimate the performance of Brazilian hospitals' services and to examine contextual variables in the socioeconomic, demographic and institutional domains as predictors of the performance levels attained. Design/methodology/approach: The paper applied a two-stage approach of the technique for order preference by similarity to the ideal solution (TOPSIS) in public hospitals in 92 Rio de Janeiro municipalities, covering the 2008–2013 period. First, TOPSIS is used to estimate the relative performance of hospitals in each municipality. Next, TOPSIS results are combined with neural networks in an effort to originate a performance model with predictive ability. Data refer to hospitals' outpatient and inpatient services, based on frequent indicators adopted by the healthcare literature. Findings: Despite a slight performance increase over the period, substantial room for improvement is observed. The most important performance predictors were related to the demographic and socioeconomic status (area in square feet and GDP per capita) and to the juridical nature and type of ownership of the healthcare facilities (number of federal and private hospitals). Practical implications: The results provide managerial insights regarding the performance of public hospitals and opportunities for better resource allocation in the healthcare sector. The paper also considers the impact of external socioeconomic, demographic and institutional factors on hospitals' performance, indicating the importance of integrative public health policies. Originality/value: This study displays an innovative context for applying the two-stage TOPSIS technique, with similar efforts not having been identified in the healthcare literature.